2020
DOI: 10.1111/1911-3838.12220
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Disclosure by the Companies on the S&P/TSX 60 Index

Abstract: Cybersecurity has become a topic of great interest since 2010. Accounting issues surrounding cybersecurity governance, management, and disclosure have gained attention from accounting standard setters, large accounting firms, and professional associations, but only a limited number of studies have looked at cybersecurity disclosure. In this study, we examine whether the content of cybersecurity disclosures of Canadian firms comprising the S&P/TSX 60 index is aligned with best practices—that is, financial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 17 publications
2
22
0
4
Order By: Relevance
“…Following the SEC's footsteps, Canadian Securities Administrator (CSA) emphasized the cybersecurity issued a notice in 2016 to the issuers, registrants and regulated entities guiding CSD (Radu and Smaili, 2021). Based on a content analysis of various Canadian companies' disclosures (e.g., annual information forms, annual and quarterly MD&A), Héroux and Fortin (2020) demonstrated that level of CSD is low, and the information is often generic.…”
Section: Research On Csd: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the SEC's footsteps, Canadian Securities Administrator (CSA) emphasized the cybersecurity issued a notice in 2016 to the issuers, registrants and regulated entities guiding CSD (Radu and Smaili, 2021). Based on a content analysis of various Canadian companies' disclosures (e.g., annual information forms, annual and quarterly MD&A), Héroux and Fortin (2020) demonstrated that level of CSD is low, and the information is often generic.…”
Section: Research On Csd: Literature Reviewmentioning
confidence: 99%
“…The sample period starts from 2014 as the concept of CSD is relatively new in the global context. Prior studies (e.g., Gao et al, 2020;Héroux and Fortin, 2020;Radu and Smaili, 2021) noted that CSD as a reporting practice became more pronounced between 2016 to 2018. 3 Also, as evidenced by Mazumder and Sobhan (2021), the focus on cyber risk governance and disclosures in Bangladesh got significant momentum after the BB heist in 2016.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…‫رل‬ ‫بتصيلبحتصث‬ ‫ا‬ ‫لنالبح‬ ‫ي‬ ‫يلبح‬ ‫ت‬ (Hilary et al, 2016;Berkman et al, 2018;Frank et al, 2019;Heroux & Anne, 2020;Kelton & Pennington, 2020;Badawy,…”
Section: ‫(وفرعياته)‬ ‫الرتيسي‬ ‫الفرض‬ ‫اشتقا‬ ‫و‬ ‫األسهم،‬ ‫في‬ ‫ا...unclassified